2023
DOI: 10.1002/anie.202307160
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Heteroatom‐Hydrogen Bonds Bridging Electron Transport in Covalent Organic Framework‐Based Supramolecular System for Photoreduction of CO2

Abstract: Supramolecular systems consisting of covalent organic frameworks (COFs) and Ni complex are designed for robust photocatalytic reduction of CO 2 . Multiple heteroatom-hydrogen bonding between the COF and Ni complex is identified to play a decisive role in the photoexcited electron transfer across the liquidsolid interface. The diminution of steric groups on COF or metal complex can optimize catalytic performance, which is more attributable to the enhanced hydrogenbond interaction rather than their intrinsic act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…As shown in Figure g, upon exposure to CO 2 and water vapor, monodentate carbonate (m-CO 3 2– , at 1397, 1463, and 1520 cm –1 ), bidentate carbonate (b-CO 3 2– , at 1263 cm –1 ), and bicarbonate (c-CO 3 2– , at 1743 cm –1 ) were identified. , The peaks at 1693 cm –1 can be attributed to asymmetric stretching of *HCO 3 – . Characteristic peaks that emerged at 1644 cm –1 can be attributed to the formation of COOH*, which was a critical intermediate during the photochemical conversion from CO 2 to CO. , …”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…As shown in Figure g, upon exposure to CO 2 and water vapor, monodentate carbonate (m-CO 3 2– , at 1397, 1463, and 1520 cm –1 ), bidentate carbonate (b-CO 3 2– , at 1263 cm –1 ), and bicarbonate (c-CO 3 2– , at 1743 cm –1 ) were identified. , The peaks at 1693 cm –1 can be attributed to asymmetric stretching of *HCO 3 – . Characteristic peaks that emerged at 1644 cm –1 can be attributed to the formation of COOH*, which was a critical intermediate during the photochemical conversion from CO 2 to CO. , …”
Section: Resultsmentioning
confidence: 90%
“…52,53 The peaks at 1693 cm −1 can be attributed to asymmetric stretching of *HCO 3 − . 53 Characteristic peaks that emerged at 1644 cm −1 can be attributed to the formation of COOH*, which was a critical intermediate during the photochemical conversion from CO 2 to CO. 54,55 Furthermore, DFT calculations were carried out to investigate the CO 2 photoreduction mechanism of IL200@ MOF-526. The geometries of the fully optimized MOF-526 and IL200@MOF-526 are shown in Figure S19.…”
Section: Mechanism Studymentioning
confidence: 99%
“…Up to now, COFs have great potential for various applications, including gas adsorption and separation, sensing, heterogeneous catalysis, energy storage and other aspects. 32–39 Furthermore, numerous research findings have indicated that two-dimensional (2D) COFs possess excellent semiconductor properties and are a new type of superior photocatalysts, particularly for hydrogen generation via water splitting. As metal-free semiconductor photocatalysts, the advantages of 2D-COFs can be described as follows: first, one-dimensional nanopores with large surface area provide space for transport, action and transformation of matter, and also increase exciton utilization.…”
Section: Introductionmentioning
confidence: 99%
“…The ΔA intensity of excited-state absorption bands in Az/rGO/Hz-COF was remarkably lower than that of Az-COF and Hz-COF, indicating the relatively lower recombination of photogenerated charges . Such a phenomenon also suggests an intermolecular electron transfer over Az/rGO/Hz-COF. The faster decay kinetics fitted by biexponential functions in Az/rGO/Hz-COF evidence a rapid charge transfer (Figure d and Supplementary Table S1). The τ 2 lifetime represents charge recombination.…”
mentioning
confidence: 95%